The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3758/s13421-016-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of animacy on metamemory

Abstract: Previous research has shown that the animacy quality of materials affects basic cognitive processes such as memory (i.e., animate stimuli are remembered better than are inanimate stimuli). This is referred to as the animacy effect. Little research has examined, however, whether this effect can be extended to higher cognitive processes such as metamemory.In the present studies, we investigated the influence of animacy on judgments of learning (JOLs) and the underlying basis of the animacy effect, namely, proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 50 publications
1
33
1
Order By: Relevance
“…As important, in a follow-up experiment, word concreteness impacted participants' JOLs in accord with their beliefs, in that JOLs were higher for concrete than for abstract words. Similar outcomes have been obtained with other cues, such as word frequency (Jia et al, 2016), font size (Mueller et al, 2014), word animacy (P. Li et al, 2016), size of mental images (T. Li et al, 2017), and word pair relatedness (Mueller et al, 2013). Typically, when participants demonstrate beliefs about a cue, the cue also influences JOLs (see the General Discussion for a few exceptions), which together confirm the general hypothesis that participants' beliefs about a cue are used to construct JOLs.…”
Section: Contribution Of Beliefs To Judgments Of Learningsupporting
confidence: 75%
“…As important, in a follow-up experiment, word concreteness impacted participants' JOLs in accord with their beliefs, in that JOLs were higher for concrete than for abstract words. Similar outcomes have been obtained with other cues, such as word frequency (Jia et al, 2016), font size (Mueller et al, 2014), word animacy (P. Li et al, 2016), size of mental images (T. Li et al, 2017), and word pair relatedness (Mueller et al, 2013). Typically, when participants demonstrate beliefs about a cue, the cue also influences JOLs (see the General Discussion for a few exceptions), which together confirm the general hypothesis that participants' beliefs about a cue are used to construct JOLs.…”
Section: Contribution Of Beliefs To Judgments Of Learningsupporting
confidence: 75%
“…Instead, they suggested that their results were inconsistent with the fluency theory and they encouraged future research to further explore the fluency theory (p. 9). However, after Mueller et al's (2014) study was published, researchers started to acknowledge that fluency may play no role in the font size effect on JOLs (e.g., Ball et al, 2014;Finn & Tauber, 2015;P. Li, Jia, Li, & Li, 2016;Magreehan et al, 2016;Mueller & Dunlosky, 2017;Mueller, Dunlosky, & Tauber, 2016;Susser, Jin, & Mulligan, 2016;Susser, Panitz, Buchin, & Mulligan, 2017;.…”
mentioning
confidence: 99%
“…For example, judgments of learning and restudy decisions are affected by the belief that font size affects memory (Luna et al, ; Rhodes & Castel, ). Beliefs have been recently advocated to account for several phenomena, such as the effect of animacy (Li, Jia, Li, & Li, ), linguistic frequency (Jia et al, ), or concreteness (Witherby & Tauber, ) on judgments of learning, and have become a very popular explanation for metacognitive judgments.…”
Section: Introductionmentioning
confidence: 99%